Foreign investments in the forestry sector as a means of increasing community resilience: two case studies in Mexico. (1st December 2018) - Cooper, L.; Huff, E.
Community resilience is the sustained ability of a community to use available resources while responding to stress, as well as the ability to recover from adverse situations accounting for social vulnerability, environmental hazards, and economic conditions. As climate change increases risk and unpredictability for management and planning, understanding resilience is crucial. Focusing on Mexico, this work explores international forestry sector investments as a tool to increase resilience. This research uses interviews, surveys, and programmatic documents comparing two case studies to explore the impact of certain foreign investments on community resiliency. The resilience concepts measured include diversity, economic and ecological variability, social capital, tight feedbacks, innovation, governance overlap, and ecosystem services. Results show that such investments can increase community resilience by improving community management, resource utilization, and recovery ability in times of economic, social, or biophysical stress. La résistance communautaire est la capabilité soutenue qu'a une communauté à utiliser les ressources disponibles tout en réagissant aux effets du stress, ainsi que son aptitude à se remettre de situations adverses se traduisant en vulnérabilité sociale, en dangers environnementaux et en conditions économiques. Alors que le changement climatique augmente les risques et l'imprévisibilité de la gestion et de la planification, comprendre cette notion de résistance est crucial. En se concentrant sur le Mexique, cette étude explore les investissements du secteur forestier international en tant qu'outil pour fortifier la résistance. Cette recherche utilise des interviews, des études et des documents programmatiques comparant deux études-cas pour explorer l'impact de certains investissements étrangers sur la résistance communautaire. Les concepts de résistance mesurés comprennent la variabilité économique et écologique, la variabilité, le capital social, les retours restreints, l'innovation, les chevauchements de gestion et les services d'écosystèmes. Les résultats indiquent que de tels investissements peuvent accroître la résistance communautaire en améliorant la gestion communautaire, l'utilisation des ressources et la possibilité de se relever à l'issue de périodes de stress économique, social ou biophysique.La resiliencia comunitaria es la capacidad sostenida de una comunidad para utilizar los recursos disponibles mientras que responde a factores de estrés, así como también la capacidad de recuperarse de situaciones adversas relacionadas con la vulnerabilidad social, las amenazas ambientales y las condiciones económicas. A medida que el cambio climático aumenta el riesgo y la imprevisibilidad para la gestión y la planificación, comprender lo que es la resiliencia es crucial. Usando México como punto focal, este trabajo explora la inversión internacional en el sector forestal como una herramienta para aumentar la resiliencia. Esta investigación emplea entrevistas, encuestas y documentos programáticos que comparan dos estudios de casos, para examinar el impacto de ciertas inversiones extranjeras en la resiliencia de la comunidad. Los conceptos de resiliencia medidos incluyen la diversidad, la variabilidad económica y ecológica, el capital social, la retroalimentación ajustada, la innovación, el traslape de gobernanza y los servicios ecosistémicos. Los resultados muestran que tales inversiones pueden aumentar la resiliencia de la comunidad cuando mejoran la gestión comunitaria, la utilización de los recursos y la capacidad de recuperación en momentos de estrés económico, social o biofísico.